Concept Analysis of Self Efficacy Among Coronary Heart Disease Patients Undergoing Percutaneous Coronary Intervention - Aria Wahyuni; Setyowati Setyowati (Universitas Aisyah Pringsewu, 2022)
Mortality and morbidity due to coronary heart disease (CHD) are increasing. Patients with coronary heart disease are undergone Percutaneous Coronary Intervention (PCI) have different perceptions regarding these actions so the belief of inability to care for self is different for everyone, therefore, it is important to build the capability of patients which is called self-efficacy. The purpose of this article is to explain the definition of the concept of self-efficacy in CHD patients undergoing PCI. The method used in this concept analysis is using Walker and Avant’s concept approach. The three definitions of self-efficacy attributes are strong self-confidence in self-care, perceived ability to engage in self-care activities, and effort and ability to control risk factors. The antecedents of the self-efficacy concept of CHD patients undergoing treatment consist of age, socioeconomic, the number of coronary blockages, duration since the first PCI, health education, self-awareness, social support, depression, adherence, and physical activity. The consequence of self-efficacy increases in health status, behavior toward health, and quality of life. The conclusion of this analysis concept increases nurse knowledge about the self-efficacy of patients with CHD that undergo PCI so that it is expected can develop evidence-based nursing through nursing intervention in improving self-efficacy and also conduct further research to dig more into self-efficacy. Abstrak: Kematian dan kesakitan akibat penyakit jantung koroner (PJK) semakin meningkat. Pasien penyakit jantung koroner yang menjalani Percutaneous Coronary Intervention (PCI) memiliki persepsi yang berbeda mengenai tindakan tersebut sehingga keyakinan ketidakmampuan untuk merawat diri berbeda untuk setiap orang, oleh karena itu penting untuk membangun kemampuan pasien yang disebut efikasi diri. Tujuan dari artikel ini adalah untuk menjelaskan definisi konsep self-efficacy pada pasien PJK yang menjalani PCI. Metode yang digunakan dalam analisis konsep ini menggunakan pendekatan konsep Walker dan Avant. Tiga definisi atribut efikasi diri adalah keyakinan diri yang kuat dalam merawat diri, kemampuan diri yang dirasakan untuk terlibat dalam kegiatan perawatan diri, dan upaya dan kemampuan melakukan pengendalian terhadap faktor risiko. Anteseden konsep efikasi diri pasien PJK yang menjalani terdiri dari usia, sosial ekonomi, jumlah penyumbatan koroner, durasi sejak PCI pertama, pendidikan kesehatan yang diterima, kesadaran diri, dukungan sosial, depresi, kepatuhan, dan aktivitas fisik. Konsekuensi dari efikasi diri meningkat pada status kesehatan, perilaku terhadap kesehatan, dan kualitas hidup. Kesimpulan dari konsep analisis ini meningkatkan pengetahuan perawat tentang efikasi diri pasien PJK yang menjalani PCI sehingga diharapkan dapat mengembangkan keperawatan berbasis bukti melalui intervensi keperawatan dalam meningkatkan efikasi diri dan juga melakukan penelitian selanjutnya lebih banyak menggali efikasi diri.